Enzymatic activity of fungi isolated from Otomycosis - Lilo Sayyid, Azhar; A Kasim, Ali ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2025)
This study aimed to the extracellular enzymayic activity of fungi causing otitis externa isolated from infected individuals in Maysan Governorate on solid media. The ability of nine fungi to secrete three enzymes: phospholipase, esterase, and hemolysin was studies.The results of the current study showed that the fungi A. terreu, G. candidum, A.alternate , R.oryzae , C.cladosporioide have the ability to produce all the studied enzymes while P. chrysogenum was found to secrte esterase and phospholipase A. niger was found to produce phospholipase and hemolysin , while A.flavus and A.oryzae showed the ability to produce esterase and phospholipase.